Analisis Kinerja Keuangan Terhadap Kemampuan Penyaluran Pembiayaan Perbankan Syariah - Eko Prasetyo (Al-Musthofa: Journal of Sharia Economics, 2020)
The purpose of this study is to analyze the financial performance of Islamic banking which is measured by three variables, namely Capital Adequacy Ratio (CAR), Third Party Funds, Non Performing Financing (NPF) on Islamic Banking Financing which is listed on the Indonesia Stock Exchange. This type of quantitative research uses secondary data. The population of this study were 16 companies with a sample of 10 companies with a research period of five years in order to obtain a sample of 50 samples. The analysis technique used in this research is Multiple Linear Regression. After testing, the results show that partially the Capital Adequacy Ratio (CAR), Third Party Funds, Non Performing Financing (NPF) have an influence on the financing of Islamic banking. Simultaneous test results based on table F show that the Capital Adequacy Ratio (CAR), Third Party Funds (DPK), Non Performing Financing (NPF) on Islamic banking financing have an influence.